A triad of infantile spasms, nystagmus and a focal tonic seizure. Issue 4 (29th August 2018) - Tarodo, Stephanie Garcia; Nguyen, Thu; Ranza, Emmanuelle; Vulliémoz, Serge; Korff, Christian M.
ABSTRACT: Epileptic spasms represent a subcategory of motor seizures that have been extensively documented and recently re‐classified by the International League Against Epilepsy as either generalized, focal or of unknown onset. Atypical characteristics continue to be reported in case studies, emphasizing the divergent morphological traits and putting into question the underlying aetiopathophysiology. Here, we report the findings of an infant with a triad of clinical manifestations during a single ictal event, comprising a cluster of epileptic spasms, vertical binocular nystagmus, and a focal tonic seizure. A video recording is presented that enabled clinical data to be correlated with EEG modifications. To date, a focal lesion has not been identified on brain imaging. The co‐occurrence of these ictal paroxysms provides insight into the anatomical localization of seizure onset and complex epileptic networks involved, and challenges the pathophysiological hypothesis for epileptic spasms, implicating cortical‐subcortical dysfunction and the implication of structures deep within the sulcus. Furthermore, the focal components both clinically and electrographically implicate involvement of the frontal eye field in the generation of vertical ictal nystagmus. [ Published with video sequence on www.epilepticdisorders.com ].